TEACHING VOCABULARY IN TRANSACTIONAL TEXT USING ROTE LEARNING - Taratika, Hedya (Journal of English Education Program, 2021)
The aim of this research is to improve students’ vocabulary in the transactional text by using Rote Learning for the seventh grade students of MTs Negeri 02 Pontianak in the academic year 2019/2020. The method used in this research is classroom action research which was conducted in two cycles. The subject of the research is 36 students of VII E class, consisting of 17 females and 19 males. In collecting the data, the researcher used observation checklist, field note, and achievement test. It was found that students’ vocabulary improved from cycle 1 to cycle 2. In the first cycle, 14.2% equal to 6 students passed the standard minimum score and it increased up to 91% or 32 students in the second cycle. By using Rote Learning in teaching vocabulary, the students could easily memorize new vocabulary. The students were actively engaged during the learning process. In short, Rote Learning is an appropriate method for the improvement of students’ vocabulary mastery.